2019
DOI: 10.1026/0932-4089/a000293
|View full text |Cite
|
Sign up to set email alerts
|

Do Social Skills Shape Career Success in the Psychology Profession?

Abstract: Abstract. Building on social capital theory, we assumed that social skills (communication skills, cooperation skills) are essential for successful career development, particularly in social professions. Applying a mixed-method approach, we integrate data from a questionnaire study with 164 psychologists (Study 1) and an interview study with 20 psychologists (Study 2). In Study 1, we found communication skills to be related to objective career success (salary, position), whereas cooperation skills were associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Otto et al reflect on the specific relevance of social interactions for psychologists who work mostly with people either individually (e.g., in therapy, coaching, or personnel selection) or as part of a group (e.g., in conflict mediation or team intervention). Hence, it can be assumed that psychologists in particular build the meaning of their work through social interactions with clients and patients3, 4 ) . In this research, based on the “Stress-as-Offense-to-Self” (SOS) concept5, 6 ) , we assume illegitimate tasks impair job satisfaction by lowering a person’s perceived appreciation in the workplace.…”
Section: Introductionmentioning
confidence: 99%
“…Otto et al reflect on the specific relevance of social interactions for psychologists who work mostly with people either individually (e.g., in therapy, coaching, or personnel selection) or as part of a group (e.g., in conflict mediation or team intervention). Hence, it can be assumed that psychologists in particular build the meaning of their work through social interactions with clients and patients3, 4 ) . In this research, based on the “Stress-as-Offense-to-Self” (SOS) concept5, 6 ) , we assume illegitimate tasks impair job satisfaction by lowering a person’s perceived appreciation in the workplace.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of graduates to communicate effectively can have a significant impact on their career development ( Masduki and Zakaria, 2020 ). Research by Otto et al (2019) ascertains that communication skills are associated with objective career success, including salary and position ( Otto et al, 2019 ). The improvement of communication skills can promote engineering students to actively participate in extracurricular activities organized by the academic institution or the student union.…”
Section: Theoretical Model and Research Hypothesesmentioning
confidence: 99%
“… Bartram and Roe (2005) found that these different fields, however, have something in common, namely that psychologists work with people, either with individuals (e.g., conducting a therapy), with loose groups (e.g., teaching classes to students), or with fixed teams (e.g., doing trainings in organizations). Thus, social interactions are part of the job of psychologists ( Otto et al, 2019 ). Sobiraj, Schladitz, and Otto (2016) suggested that psychologists put a high value on receiving appreciation, which could be considered one of the most striking aspects of human nature.…”
Section: Positive Social Interactions: Appreciation As a Job Resourcementioning
confidence: 99%
“…As outlined before, the psychological profession involves contact with other people, either supervisors, coworkers, or, depending on the field (i.e., therapist or consultant), with clients or patients. Thus, social interactions are part of everyday life for many psychologists ( Otto et al, 2019 ). When these social interactions are affected by conflicts or a negative climate, they might be perceived as social stressors.…”
Section: Negative Social Interactions: Social Stressors and (Further)mentioning
confidence: 99%